The Effectiveness of Using Educaplay Media with a Deep Learning Approach to Improve Students' Critical Thinking Skills - Putri, Candra Avista; Hanifah, Nur Hidayah; Syaifuddin, Ahmad (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3778, 2025)
Social studies subjects, which are only dominated by memorization and one-way lectures, make students passive and have difficulty relating to real life, so they require innovation in learning methods to optimize students' critical thinking skills. The purpose of this study is to determine the influence of the use of Educaplya media with a Deep Learning approach on students' thinking ability in elementary school. The method of this study is quantitative, with a Quasi Experimental Control Group Design approach. The subjects in this study were 44 grade VI students, which were divided into control and experimental classes. The data collection techniques carried out were observation, interviews, and tests. Data analysis used the Independent Sample t-test with the prerequisites of normality and homogeneity tests. The results of the Independent Sample t-test in the statistical test showed that the gain of sig values was 0.000 < 0.05 so that it can be stated that there is an influence of the use of Educaplay media on students' critical thinking skills. This study provides recommendations for educators in elementary schools to utilize technology with an approach that is in accordance with the needs and developments of the times. For example, Educaplay can be used as a support during the learning process.